Birth prevalence and parental stress associated with neural tube defects in Amhara’s public comprehensive specialized hospitals, Ethiopia, 2024 - Hailemariam Gezie; Endalk Birrie Wondifraw; Muluken Amare Wudu; Habtam Gelaye; Fekadeselassie Belege Getaneh (PLoS ONE, 2025)
Background Neural tube defects (NTDs) are severe congenital anomalies resulting from the incomplete closure of the embryonic neural tube, affecting around 300,000 newborns globally each year and leading to significant mortality and disability. While high-income countries have seen a reduction in NTD prevalence, developing nations like Ethiopia continue to face high rates. Families impacted by NTDs often endure emotional challenges, including grief, anxiety, and social isolation. This study aims to investigate the birth prevalence of NTDs and the associated parental stress, emphasizing the wider effects on families. Methodology An institution-based cross-sectional study was conducted in Dessie and Deber Berhan comprehensive specialized hospitals from July 24, 2023, to July 24, 2024, to evaluate the birth prevalence of NTDs and the associated parental stress among parents of children aged 1 month to 12 years diagnosed with NTDs. A total of 308 parent-child pairs participated in the study. Data were gathered using a pretested questionnaire and an 18-item Parenting Stress Scale. Statistical analysis was performed using Stata version 17, where linear regression was utilized to identify significant predictors after verifying the necessary assumptions. The findings were presented in multiple formats for clarity and comprehensibility. Results The overall birth prevalence of neural tube defects was found to be 0.0052 (95% CI: 0.0038, 0.0067), which translates to 52 cases per 10,000 deliveries. Key factors associated with increased parental stress included being a mother (β = 2.51), older parental age (β = 0.18), the child’s age (β = 0.81), a prior history of having children with NTDs (β = 7.88), and the presence of a ventriculoperitoneal shunt in the child (β = 4.66). Conclusion The findings of this study indicate that the birth prevalence of NTDs is becoming a significant public health concern. Additionally, several factors contributing to increased parental stress were identified, including older parental age, the child’s age, a previous history of NTDs in siblings, and the presence of a ventriculoperitoneal shunt. These results highlight the urgent need for targeted support and resources for affected families to help mitigate the psychological impact associated with these conditions.